Missed Nursing Care During Labor and Birth and Exclusive Breast Milk Feeding During Hospitalization for Childbirth. Issue 5 (September 2020) - Simpson, Kathleen Rice; Lyndon, Audrey; Spetz, Joanne; Gay, Caryl L.; Landstrom, Gay L.
Abstract: Purpose: The purpose of this study was to determine associations between missed nursing care and nurse staffing during labor and birth, and exclusive breast milk feeding at hospital discharge. Study Design and Methods: Labor and birth nurses in three states were surveyed about missed nursing care and their maternity units' adherence to the AWHONN (2010) nurse staffing guidelines for care during labor and birth, using the Perinatal Misscare Survey. Nursing responses were aggregated to the hospital level and estimated associations between missed nursing care, nurse staffing, and hospitals' exclusive breast milk feeding rates were measured using The Joint Commission's Perinatal Care Measure (PC-05). Results: Surveys from 512 labor nurses in 36 hospitals were included in the analysis. The mean exclusive breast milk feeding rate was 53% (range 13%–76%). Skin-to-skin care, breastfeeding within 1 hour of birth, and appropriate recovery care were on average occasionally missed (2.33 to 2.46 out of 4; 1 = rarely, 2 = occasionally, 3 = frequently, or 4 = always) and were associated with PC-05 [B(CI) -17.1(-29, -6.3), -17.9(-30.5, -6.2), and -15.4(-28.7, -2.1), respectively]. Adherence with overall staffing guidelines was associated with PC-05 [12.9(3.4, 24.3)]. Missed nursing care was an independent predictor of PC-05 [-14.6(-26.4, -2.7)] in a multilevel model adjusting for staffing guideline adherence, perceived quality, mean age of respondents, and nurse burnout. Clinical Implications: Exclusive breast milk feeding is a national quality indicator of inpatient maternity care. Nurses have substantial responsibility for direct support of infant feeding during the childbirth hospitalization. These results support exclusive breast milk feeding (PC-05) as a nurse-sensitive quality indicator. Abstract : When maternity nurses are caring for women in the context of inadequate nurse staffing, important aspects of nursing care may be missed, delayed, or incomplete. The concept of missed nursing care is increasingly being applied to maternity, neonatal and pediatric nursing settings after many years of focus on medical-surgical units in acute care hospitals. In this study missed nursing care and inadequate nurse staffing were found to be associated with exclusive breast milk feeding during the childbirth hospitalization.